Early palmar plate fixation of distal radius fractures may benefit patients aged 50 years or older: a randomized trial comparing 2 different treatment protocols - Sirniö, Kai; Leppilahti, Juhana; Ohtonen, Pasi; Flinkkilä, Tapio (Acta Orthopaedica, 2019)
Background and purpose — There is no consensus regarding optimal treatment of displaced distal radius fractures (DRFs). We compared the results of 2 treatment protocols: early palmar plating vs. primary nonoperative treatment of displaced DRFs. Patients and methods — We performed a prospective randomized controlled study including 80 patients aged ≥ 50 years with dorsally displaced DRFs, excluding AO type C3 fractures. Patients were randomized to undergo either immediate surgery with palmar plating (n = 38), or initial nonoperative treatment (n = 42) after successful closed reduction in both groups. Delayed surgery was performed in nonoperatively treated patients showing early loss of alignment (n = 16). The primary outcome measure was Disabilities of the Arm, Shoulder, and Hand (DASH) score. Results — Mean DASH scores at 24 months in the early surgery group were 7.9 vs. 14 in the initial nonoperative group (difference between means 6, 95% CI 0.1–11, p = 0.05). Delayed operation was performed on 16/42 of patients due to secondary displacement in the initial nonoperative group. In “as treated” analysis, DASH scores were 7 in the early surgery group, 13 in the nonoperative group, and 17 after delayed surgery (p = 0.02). The difference in DASH scores between early and delayed surgery was 9 points (CI 0.3–19, p = 0.02) Interpretation — Treatment of DRFs with early palmar plating resulted in better 2-year functional outcomes for ≥ 50-year-old patients compared with a primary nonoperative treatment protocol. Delayed surgery in case of secondary displacement was not beneficial in terms of function.